A checklist and key to the snakes of the genus Geophis (Squamata: Colubridae: Dipsadinae), with commentary on distribution and conservation - Wilson, Larry David; Townsend, Josiah H. (Zootaxa, 2007)
Geophis Wagler is the fourth largest genus of colubrid snakes in the Western Hemisphere, with 46 species currently recognized. Since the last major treatment of this genus, there have been 12 new species described, three taxa elevated to the species level, and two taxa previously recognized at the species level synonymized with other taxa. We present a checklist for the genus Geophis, summarizing information on taxonomic history, type material and locality, distribution, and species group assignment for 46 species. We also provide an identification key for the 46 species, followed by a brief analysis of distributional patterns and conservation status.